The DsTau Experiment: A Study for Tau-Neutrino Production - Mădălina Mihaela Miloi; [DsTau Collaboration] (Particles, 2020)
For clarifying the validity of the Lepton Universality hypothesis, one of the fundamental statements of the Standard Model, the interaction cross section for all three flavors of leptons have to be known with high precision. In neutrino sector, for electron and muon neutrinos, the interaction cross section is known fairly well, but for tau neutrino only poor estimations exist. In particular, the most direct measurement by the DONuT experiment was performed with rather poor accuracy due to low statistics and an uncertainty of the tau neutrino flux. The DsTau experiment proposes to study tau-neutrino production process and thus to improve significantly the accuracy of calculations of tau neutrino flux for neutrino accelerator experiments. To study reactions providing most of tau neutrinos, the experiment uses a setup based on high resolution nuclear emulsions, capable to register short lived particle decays created in proton-nucleus interactions. The present report is an overview of the DsTau experiment together with some of the preliminary results from the pilot run.